Konsep Kalam Khabari dan Insya’i Al-Qur`An untuk Komunikasi Pembelajaran Pendidikan Agama Islam - Husnayati, Uus Maulidah; Ainusyamsi, Fadlil Yani (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2017)
The entire text of the Qur'an is kalām khabari and insha`i with varying presentation according to the form of the arrangement to be built, the conformity with the context, and what kind of beauty is served. Variety of patterns presented this course has a variety of communication purposes. Furthermore, the pattern and style of the Qur'an editorial are imitated as the patterns of language communication in the learning process of Islamic Religious Education, between teachers and learners. Editorial patterns and objectives that can be extracted indicate that the Qur'an presents systematically systemic and systemic learning patterns, encouraging the selection of appropriate methods, providing confirmation in the form of repetition or additional information, conveying forms of command, prohibition, motivation and persuasion with persuasion educative, attention to the level of ability of learners, and encourage to think.